دور الرقابة الداخلية في دعم آليات الحوكمة في الشركات الاقتصادية – دراسة عينة من الشركات على مستوى ولاية الشلف (2023)-: The role of internal control in supporting governance mechanisms in economic companies – study of a sample of companies in Wilaya of Chlef (2023) - بشير إلزعر حسين; كنزة بن غالية (Journal of North African Economies, 2025)
The study aims to demonstrate the role of internal control in supporting the governance of organizations in Algeria. To achieve this goal, reliance was placed on a combination of deductive and inductive approaches, with their tools of description and analysis. A questionnaire was also designed and distributed to a sample of executives in the companies under study, and after retrieving it, it was analyzed using a program. Statistical packages for the social sciences (SPSS), and extracting the necessary results that benefit the study. Finally, a number of results and recommendations were presented and horizons for the study were set that could be future research topics.